2010
DOI: 10.1007/s00280-009-1239-7
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of S-1 and docetaxel for previously treated patients with locally advanced or metastatic non-small cell lung cancer

Abstract: The combination of S-1 and docetaxel is well tolerable and has substantial activity for patients with locally advanced or metastatic non-small cell lung cancer. A phase III trial comparing docetaxel with or without S-1 would warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
(28 reference statements)
0
10
5
Order By: Relevance
“…In addition, a previous study has reported that the combination of 80 mg m −2 S-1 per day for 14 consecutive days and 35 mg m −2 docetaxel on days 1 and 15 every 4 weeks (Figure 1B) in patients with previously treated advanced NSCLC achieved ORRs of 16.3% with median PFS time of 3 months, MST of 9 months, and 1-year survival rates of 42%, respectively (Oki et al , 2011). Our response rates and median PFS time were slightly higher than those of studies reported by Atagi et al , 2008, Yanagihara et al , 2010, and Oki et al , 2011.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…In addition, a previous study has reported that the combination of 80 mg m −2 S-1 per day for 14 consecutive days and 35 mg m −2 docetaxel on days 1 and 15 every 4 weeks (Figure 1B) in patients with previously treated advanced NSCLC achieved ORRs of 16.3% with median PFS time of 3 months, MST of 9 months, and 1-year survival rates of 42%, respectively (Oki et al , 2011). Our response rates and median PFS time were slightly higher than those of studies reported by Atagi et al , 2008, Yanagihara et al , 2010, and Oki et al , 2011.…”
Section: Discussioncontrasting
confidence: 91%
“…Two previous studies have reported that docetaxel at a dose of 40 mg m −2 on day 1 and S-1 at a dose of 80 mg m −2 per day on days 1–14 every 3 weeks (Figure 1A) in patients with previously treated advanced NSCLC achieved ORRs of 24.1 and 18.4% with median PFS times of 3.9 months and 4.4 months, respectively. Moreover, their MSTs and 1-year survival rates were 11.8 months and 16.1 months, and 42 and 60%, respectively (Atagi et al , 2008; Yanagihara et al , 2010). In addition, a previous study has reported that the combination of 80 mg m −2 S-1 per day for 14 consecutive days and 35 mg m −2 docetaxel on days 1 and 15 every 4 weeks (Figure 1B) in patients with previously treated advanced NSCLC achieved ORRs of 16.3% with median PFS time of 3 months, MST of 9 months, and 1-year survival rates of 42%, respectively (Oki et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chemotherapy-naïve patients, S1 in combination with gemcitabine showed a response rate of 23.1–30.6%, with an MST of 15.5–18.8 months [20]. When combined with docetaxel, a response rate of 18.4%, a median PFS of 4.4 months and an MST of 16.1 months were reported for previously treated NSCLC patients [21]. These results are comparable to those of standard platinum-based regimens.…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis showed that postoperative adjuvant chemotherapy with UFT significantly improved 5-and 7-year survival (Hamada et al 2005). Several recent phase II clinical trials suggested that S-1-based chemotherapy showed favorable clinical efficacy and mild toxicities, regardless of treatment with single agent S-1 or an S-1-based combination regimen (Kawahara et al 2001;Yanagihara et al 2010). Therefore, we conducted a metaanalysis to further assess the advantages and toxicity profile of S-1-based chemotherapy versus standard chemotherapy for the treatment of patients with locally advanced or metastatic NSCLC.…”
Section: Introductionmentioning
confidence: 99%